Environmental security in focus of Central Asian countries interests (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Current environmental situation in Central Asia, causes of environmental degradation, environmental impact on regional security were considered in the article. The author focuses on water and land resources, environmental consequences of their irrational using and other problems. It was noted that Central Asian countries have already made progress indifferently by collaborating in the field of management and sustainable use of common natural resources. They succeeded in avoiding obvious interstate conflicts and nowadays countries are participating in regular negotiations on sharing water resources and implementing various cooperation initiatives. However, an acute shortage of domestic resources to address environmental issues shows that it is necessary to support environmental cooperation by foreign aid. Joint actions of Central Asian countries can be implemented more efficiently with involvement of international organizations and donors that can be guarantors of agreements.